Crestwood Heights A North American Suburb - Seeley, John R.; Loosley, Elizabeth W.; Sim, R. Alexander (Heritage, 2019)
Crestwood Heights is a study of a well-known Canadian community. It is located within the borders of one of Canada's big cities; its name symbolizes success, wealth, and social prestige; its inhabitants possess as many of the "good things of life" as most human beings ever aspire to. This penetrating study of how the people of "Crestwood Heights" live, how they raise and educate their children, how they compete socially and economically, is of absorbing interest --